3i(7i-5)=0

Simple and best practice solution for 3i(7i-5)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3i(7i-5)=0 equation:


Simplifying
3i(7i + -5) = 0

Reorder the terms:
3i(-5 + 7i) = 0
(-5 * 3i + 7i * 3i) = 0
(-15i + 21i2) = 0

Solving
-15i + 21i2 = 0

Solving for variable 'i'.

Factor out the Greatest Common Factor (GCF), '3i'.
3i(-5 + 7i) = 0

Ignore the factor 3.

Subproblem 1

Set the factor 'i' equal to zero and attempt to solve: Simplifying i = 0 Solving i = 0 Move all terms containing i to the left, all other terms to the right. Simplifying i = 0

Subproblem 2

Set the factor '(-5 + 7i)' equal to zero and attempt to solve: Simplifying -5 + 7i = 0 Solving -5 + 7i = 0 Move all terms containing i to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + 7i = 0 + 5 Combine like terms: -5 + 5 = 0 0 + 7i = 0 + 5 7i = 0 + 5 Combine like terms: 0 + 5 = 5 7i = 5 Divide each side by '7'. i = 0.7142857143 Simplifying i = 0.7142857143

Solution

i = {0, 0.7142857143}

See similar equations:

| 9000(46)=55x | | 1.6z+14=2z-2 | | 6-(-5+4i)-(-13-I)=0 | | 1.6z+18=2z-2 | | (y-11)+(y+8)=6y | | 3(r+1)-2(3-2r)-3(3-r)=2(r+5)-4 | | =60ln(x+1) | | (3+2i)-(5-7i)=0 | | 35n-4=66 | | 3w^2=-27w | | 8X+30=10X | | -5(z-9)(-z-3)=0 | | 5z+16=4z-10 | | 2X-30-X=30-4X | | -4z(z-3)(z-9)=0 | | 15x-52=5x+18 | | x^2+10x-73= | | x^2+10x-73= | | 10X=9+4X+51 | | x^2+10x-73=0 | | (y-4)(y+8)=0 | | x^2+6x-73=0 | | 17x-(6x-4)=48 | | 2(x-18)=-2 | | -4x+66=3x+38 | | 4+3*2=14 | | 3x-10+5x+10=180 | | -3y-3=2-2y | | x+x^2=25.862 | | y+1x+0=2 | | 7x+11=3x+79 | | -6v-6(2x-4)=84 |

Equations solver categories